Teknik Skoring dan Penilaian dalam Evaluasi Pembelajaran di Abad 21, Serta Implikasinya dalam Bimbingan dan Konseling - Nurul Alifah; Adinda Dwi Cahyani; Dea Kartika Utami; Ully Arta Silitonga; Minarsi Minarsi (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the role of scoring techniques in learning evaluation and their implications for Guidance and Counseling (BK) services. The method used was a Systematic Literature Review (SLR) by examining several scientific articles published between 2015 and 2025. The results of the study indicate that scoring techniques, whether conventional, penalty, compensatory, or rubric, have their respective advantages and limitations. Selecting the right technique can increase the objectivity, validity, and reliability of the evaluation, ensuring that the results truly reflect student abilities. In the context of BK, scoring techniques are not only relevant for assessing academic achievement but are also useful in non-test assessments such as attitudes, interests, motivation, and stress levels. The integration of test and non-test assessments allows counselors to obtain a comprehensive picture of student development, which then forms the basis for designing interventions and service strategies, and supporting holistic student character development.